Exploration of Perceptions of Dog Bites among YouTube™ Viewers and Attributions of Blame. (3rd September 2018) - Owczarczak-Garstecka, Sara C.; Watkins, Francine; Christley, Rob; Yang, Huadong; Westgarth, Carri
ABSTRACT: Dog bites are a human public health and dog welfare problem. This qualitative study is the first to use YouTube ™ to examine how viewers perceive risk of, and attribute blame for, dog bites. Comments underneath 10 videos, chosen to represent a diversity of dog-bite scenarios, were analyzed inductively using thematic analysis. Six themes emerged: 1) Commentators thought that dogs are inherently good-natured but wild animals and emphasized how dogs try to avoid biting people; 2) all recognized breeds of dogs were stereotyped and breed stereotypes were used to shift the blame away from the dog and onto a bite victim, unless the dog identified in a video was a pit bull type. The dog was often blamed in such case; 3) It was argued that a breed limits the extent to which a dog can be trained and controlled; 4) Owners/handlers were often blamed for bites due to their inability to control the dog, and commentators identified the need for appropriate training and socialization in order to control dogs and reduce bite risk; 5) Bite victims were also blamed for the bites when their behavior was perceived as provoking a dog. Although children's behavior was identified as causing a risk, parents of children bitten in the videos were blamed for bites instead due to their approach to child supervision; 6) Bites in a range of contexts, such as play or when viewers thought that the victim's behavior provoked a dog, were seen as well-de-served and normal. It was concluded that although comments on publicly available videos need to be interpreted with caution due to a self-selection bias, their analysis can help to identify attitudes and perceptions towards risk around dogs that could aid bite prevention interventions and policies.